3, 3′-diindolylmethane exerts antiproliferation and apoptosis induction by TRAF2-p38 axis in gastric cancer. Issue 2 (February 2021) - Ye, Yang; Ye, Fen; Li, Xue; Yang, Qi; Zhou, Jianwei; Xu, Wenrong; Aschner, Michael; Lu, Rongzhu; Miao, Shuhan
Abstract : 3, 3′-diindolylmethane (DIM), an active phytochemical derivative extracted from cruciferous vegetables, possesses anticancer effects. However, the underlying anticancer mechanism of DIM in gastric cancer remains unknown. Tumor necrosis factor (TNF) receptor-associated factor 2 (TRAF2), one of the signal transduction proteins, plays critical role in proliferation and apoptosis of human gastric cancer cells, but there are still lack of practical pharmacological modulators for potential clinical application. Here, we further explored the role of TRAF2 in inhibiting cell proliferation and inducing apoptosis by DIM in human gastric cancer BGC-823 and SGC-7901 cells. After treating BGC-823 and SGC-7901 cells with DIM for 24 h, cell proliferation, apoptosis and TRAF2-related protein were measured. Our findings showed that DIM inhibited the expressions of TRAF2, activated p-p38 and its downstream protein p-p53, which were paralleled with DIM-triggered cells proliferation, inhibition and apoptosis induction. These effects of DIM were reversed by TRAF2 overexpression or p38 mitogen-activated protein kinase (MAPK)-specific inhibitor (SB203580). Taken together, our data suggest that regulating TRAF2/p38 MAPK signaling pathway is essential for inhibiting gastric cancer proliferation and inducing apoptosis by DIM. These findings broaden the understanding of the pharmacological mechanism of DIM's action as a new modulator of TRAF2, and provide a new therapeutic target for human gastric cancer.